2010
DOI: 10.1063/1.3491416
|View full text |Cite
|
Sign up to set email alerts
|

Prediction for room-temperature half-metallic ferromagnetism in the half-fluorinated single layers of BN and ZnO

Abstract: On the basis of density functional calculations we explored the possibility that BN and ZnO single layers can become ferromagnetic at room temperature and half-metallic upon fluorine adsorption. Fluorine atoms form stable bonds only with the B and Zn atoms on the graphenelike BN and ZnO single layers, respectively, and the resulting fluorinated BN and ZnO single layers are expected to become ferromagnetic half metals with Curie temperatures around room temperature. The fluorination of semiconductor single laye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
51
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 19 publications
1
51
0
Order By: Relevance
“…[1] Considerable research activities have been devoted to search for half metallic materials that can generate 100% spin-polarized currents at the Fermi level, making them suitable for the spintronic devices. [5][6][7][8][9][10] In analogy to graphene and BN, graphitic-C 3 N 4 (g-C 3 N 4 ) is of interest due to its promising potential applications in the field of photocatalysis. Monolayer materials have the particular dimensionality, compared with their bulk counterparts, and hence exhibit different properties, such as electricity, optics, magnetism and mechanics.…”
Section: Introductionmentioning
confidence: 99%
“…[1] Considerable research activities have been devoted to search for half metallic materials that can generate 100% spin-polarized currents at the Fermi level, making them suitable for the spintronic devices. [5][6][7][8][9][10] In analogy to graphene and BN, graphitic-C 3 N 4 (g-C 3 N 4 ) is of interest due to its promising potential applications in the field of photocatalysis. Monolayer materials have the particular dimensionality, compared with their bulk counterparts, and hence exhibit different properties, such as electricity, optics, magnetism and mechanics.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15] The published studies on the possible magnetic properties of fluorinated BNNSs (F-BNNSs) or boron nitride nanotubes (F-BNNTs) are of theoretical nature. Kan et al [18] demonstrated the possibility that single-layer BNNS can become ferromagnetic at room temperature and half-metallic upon fluorine adsorption. Zeng et al [17] investigated the electron structure and the transport properties of fluorinated zigzag-edged boron nitride nanoribbons, showing that the transition between a half-metal and a semiconductor in the nanoribbons can be realized by fluorination at different sites or by changing the fluorination level.…”
mentioning
confidence: 99%
“…Particularly, FM, the important property for the application of 2D materials in spintronic devices, was predicted in half-brominated silicone 26 and half-uorinated BN and ZnO sheets. 27 Nevertheless, experimental realisation of promising spin with the methods mentioned above still is difficult because precise modulations of vacancy, doping, strain and surface-functionalization on 2D structures is still challenging. Recently, there has been an increasing interest for exploring 2D structures with intrinsic magnetism.…”
Section: Introductionmentioning
confidence: 99%
“…Great efforts have been made in order to explore the application of 2D structures in this eld. [19][20][21][22][23][24][25][26][27] and using strain in defect-interacted MoS 2 sheet, 25 have been conrmed as effective methods to generate spin. Particularly, FM, the important property for the application of 2D materials in spintronic devices, was predicted in half-brominated silicone 26 and half-uorinated BN and ZnO sheets.…”
Section: Introductionmentioning
confidence: 99%